Dynamics effect of volatility index, interest rates, and commodity prices on Indonesian bond yields - Darsono, Susilo Nur Aji Cokro; Firman, Afrizal; Nugraha, Pazri; Isnaini, Nurul (Jurnal Ekonomi & Studi Pembangunan, 2024)
Several factors influence the movements and dynamics of bond yields in financial markets. The determination of monetary policy, specifically the decisions regarding interest rates made by central banks, is a critical factor. Moreover, bond yields can be influenced by various factors such as geopolitical events, financial volatility, market sentiment, and investor risk appetite. These factors can impact the demand and supply dynamics in bond markets. This research aims to analyze the influence of Interest Rates, IDR to USD Exchange Rates, Volatility Index (VIX), Gold and Oil Prices on Bond Yields in Indonesia. The data used in this research is secondary data, which consists of time series data from 2019-2023. This research investigates the impact of financial and commodity prices on bond yields in Indonesia by using the autoregressive distributed lag (ARDL) model to examine both the long-run correlation and short-run effect. Empirical results found that Interest Rate, Volatility Index (VIX), and Oil Prices have a significant positive influence. Meanwhile, the Gold Price variable has a significant negative influence. This research has several crucial policy implications for investors concerning the national monetary policy, exchange rate fluctuation, and global volatility index to create profitable and sustainable portfolio strategies. Moreover, investment managers and investors should be concerned about the global commodities prices that will affect bond yield performances. This research contributes to the recent literature presenting causal relations of global volatility index (VIX) on Indonesian bond yield.